The Ecological Challenge of Peace Education: A plea for a new Comprehensive Peace Education (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
The ecological challenge does not just mean the challenge of ecological problems and crises. Rather, it refers to the epistemic challenge of developing a new way of thinking, a new relationship to “nature” and thus also to the human world, which could be described as eco-relational peace. This text traces the paths that peace education has taken over the last half century in developing such a way of thinking.Ecological issues have long played a role in peace education and peace research in general. This connection began at the latest with Hiroshima and Nagasaki – in other words, with the realization that humanity itself is capable of destroying the foundations of life. As far as environmental issues in the narrower sense are concerned, the work of Anita Wenden and Frans Verhagen, but also of Betty Reardon  in the USA or the German handbook Practice of Ecological and Peace Education in Germany Deutschland in the 1980s come to mind.What is new, however, is that ecology is no longer just a topic, but has become a category of peace. Added to this is the post-colonial and indigenous criticism not only of Western ecological concepts, but also of the Western understanding of nature – such as the work of Malcolm Ferdinand from the Caribbean or the critical studies of Western ecological thinkers by Raymond Matand Makashing from the Democratic Republic of Congo. It is increasingly recognized that issues of global justice, non-violence and peace cannot do without the dimension that some call “peace with nature”. However, these are auxiliary expressions, because there is a danger that what should be connected will be separated again by the use of the terms. For this reason, concepts such as the Anthropocene must also be seen in their ambivalence.As far as peace education itself is concerned, the work of Vanessa Andreotti from Brazil is probably trend-setting, as it not only criticizes Western concepts such as Global Citizenship Education through postcolonial and indigenous approaches, but also renews them.In this article, a number of strands from the history of ideas will be presented and examined in terms of their usefulness for a contemporary understanding of peace and peace education. The aim is to provide some building blocks for a “new comprehensive peace education”.
Keywords: Peace Education; Comprehensive Peace Education; Ecology; ecological peace